Application of Problem-Based Learning with Video Assistance to The Learning Outcomes of Science from Students in Class V Elementary - Gusmaweti; Rigel Prima Sari; Enjoni (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This study aims to determine the effect of the video-assisted Problem-based learning (PBL) model on cognitive and psychomotor aspects of learning outcomes in the question-and-answer indicators in science learning for Class V students at SD Negeri 31 Payakumbuh. This type of research is an experiment with a "posttest-only control design". The population in this study were all fifth-grade students at SD Negeri 31 Payakumbuh for the 2022/2020 academic year. The sampling technique is Total Sampling. The research instrument was in the form of valid, reliable student science learning test questions, and student learning questionnaires on psychomotor aspects. Data on student learning outcomes were analyzed using the t-test at the 5% test level. The results showed that there was a significant effect of the Video Assisted Problem Based Learning Model on Science Learning Outcomes of Class V Students, in a statistical test t hit > t tab, namely 2.30 > 2.01. the average cognitive aspect of learning outcomes in the experimental class was 82.43 and in the control class 73.03. The science learning outcomes of students in the psychomotor aspect on the indicator asking the experimental class were 65.32% and the control was 59.80%, and the indicator answering the experimental class was 83.06% and the control was 75%. It can be concluded that the application of the video-assisted Problem-Based Learning model has an effect on the science learning outcomes of fifth-grade students at SD Negeri 31 Payakumbuh in the 2022/2023 Academic Year. It is suggested that teachers who teach science in elementary schools can apply the video-assisted Problem-Based Learning model to different science materials to improve the learning process.